Assessment of positive experiences using associative learning in chickens - Manja Zupan Šemrov; Dušan Terčič; Elena Gobbo (Poultry Science)
ABSTRACT: To determine whether differences in positive experiences can influence associative learning ability, 2 tasks were conducted with 90 laying hens at the peak of the laying period. The selected hens were reared in a larger flock under the same housing conditions without perches, so they had the same rearing experiences and were moved to either enriched cages or to the floor system at 16 wk of age. They belonged to 3 breeds (Slovenian barred hen: Ba; brown hen: Br; silver hen, S), with 30 hens per breed. The predictor signal, the sound of a clicker, with a 3-second delayed reinforcer (commercial layer feed) was used to mark the desired behaviour (pecking for feed). Hens that associated feed with a clicker (85.06%) were taught 2 tasks, the colour discrimination task (CD) and the target following task (TF). In the CD, the hens had to discriminate between yellow, red and blue colors and peck at a yellow magnet only. In the TF, the desired behaviour was to follow a target, a purple ball on a stick, from 1 perch to another and peck it at the end of the perch. The main results of the hens associating the signal with feed were that the Ba hens learned faster than the S hens (P = 0.006) and required fewer clicker sounds than the Br hens in the CD (P = 0.003). Floor hens that completed CD or TF or both took less time to complete the task (CD, P = 0.03, TF, P = 0.06; both tasks, P = 0.02) or with fewer clicker sounds (CD task; P = 0.02) than cage hens. Although these results suggest that Ba hens and floor hens showed better associate learning performance, probably because they perceived their environment as more rewarding and thus potentially more positive, caution is needed in interpretation considering social experiences and that the ability to perch and the ability to move quickly on a perch can be confounded in TF and both tasks can be confounded with foraging ability.